2014 International Symposium on Computers in Education (SIIE) 2014
DOI: 10.1109/siie.2014.7017714
|View full text |Cite
|
Sign up to set email alerts
|

Motivation assessment in engineering students using hybrid technologies for 3D visualization

Abstract: This paper describes the integration of hybrid interfaces in the workflow using three-dimensional models, and presents the results of a preliminary study based on the profile and the student motivation. The study is conducted with first year Building Engineering degree students in order to use mobile technologies, augmented reality (AR) and digital sketching (DS) in different case studies. The resources developed combine traditional methods with interactive visualization of building and civil virtual models us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Five studies presented spatial displays. Three studies did not provide enough information about the system evaluated; therefore, it was not possible to classify these systems in all three categories of AR [27,28,38].…”
Section: Fig 4 Papers According To the Design Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies presented spatial displays. Three studies did not provide enough information about the system evaluated; therefore, it was not possible to classify these systems in all three categories of AR [27,28,38].…”
Section: Fig 4 Papers According To the Design Methodologymentioning
confidence: 99%
“…Mobile learning or, simply, m-learning is the didactic-pedagogical expression used to designate a new educational "paradigm" based on the use of mobile technologies [58]. Also, McGreal [55] adds that "m-learning happens in [50], [76], [17], [52], [51], [8], [28], [27], [64], [32], [37], [80], [62], [7], [31], [45], [18], [30], [20] Not mentioned [74], [70], [9] Situated learning [33], [67], [39] Cognitive theory of multimedia learning and cognitive load theory [42], [82] Cognitive load theory [73], [39] Learning styles theory [35], [38] Mobile learning context in which it is needed and relevant and is situated within the active cognitive processes of individual and groups of learners. " Thus, it takes advantage of the widely available mobile devices to provide access to learning anywhere and anytime, which changes many paradigms of traditional education.…”
Section: Fig 4 Papers According To the Design Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, students are engrossed and may be motivated to learn new skills to solve problems (Norman & Spohrer, 1996). Studies have indicated that AR can serve as a motivational factor, increasing interest and curiosity and leading to improved academic performance (Campos et al, 2011;Fonseca et al, 2014;Yechkalo et al, 2019). Numerous studies have highlighted AR's ability to provide an immersive learning environment (Lee et al, 2010;Wu et al, 2013).…”
Section: Augmented Realitymentioning
confidence: 99%
“…Fonseca et al [19] propose an AR learning process in the Building Engineering Degree in order to use mobile technologies, AR and digital sketching (DS) in different case studies.…”
Section: Introductionmentioning
confidence: 99%